From the History of the Publication of the Opera The Woman with the Dagger: Vladimir Rebikov — Boris Jurgenson — Arthur Schnitzler - Elena M. Shabshaevich (Современные проблемы музыкознания)
The article elucidates the history of the publication of Vladimir Ivanovich Rebikov’s opera The Woman with the Dagger in the Moscow-based publishing house P. Jurgenson, spanning the years 1910–1912. The context is disclosed of the creation of the work occurring at the beginning of the late period of the composer’s creativity, and a short characterization is given of the opera’s dramatic source — a play with the same title by outstanding Austrian dramaturgist and writer of the modern period of the early 20th century. The vicissitudes of the signing of the contract between the composer and the dramaturgist for the right of making use of the play leading to the two men’s resulting agreement with the publishing house are set forth in detail. Special attention is drawn to the new Russian copyright law of that time, created in 1911 with the influence of European legislation, and the rules are described that had to be followed by composers who set their music to already published texts when their works were performed outside of the Russian Empire. Light is shed on the circumstances of the creation of a new Russian libretto for the opera that simultaneously met the requirements of the law, Schnitzler’s wishes and Rebikov’s already written text (an adaptation of Lina Esbeer), the picture for the cover of the cover of the piano-vocal score (drawn by Czech artist Rudolf Adamek), as well as the details of the publication of the piano-vocal score and the brochure with the libretto by Jurgenson’s publishing house. The materials of the article are based on the correspondence of Vladimir Ivanovich Rebikov, the publisher at that time, Boris Petrovich Jurgenson and Arthur Schnitzler, the manuscripts of the opera The Woman with the Dagger (the piano-vocal score and the full orchestral score), as well as Rebikov’s biography, all of which are preserved in the archives of the Russian National Museum of Music. The epistolary is brought into scholarly use for the first time in that capacity; Schnitzler’s letters are published for the first time.